2010
DOI: 10.1103/physrevb.82.060514
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Fe and Nd magnetism in NdFeAsO single crystals

Abstract: The structural and magnetic phase transitions have been studied on NdFeAsO single crystals by neutron and x-ray diffraction complemented by resistivity and specific heat measurements. Two low-temperature phase transitions have been observed in addition to the tetragonal-to-orthorhombic transition at TS ∼ 142 K and the onset of antiferromagnetic (AFM) Fe order below TN ∼ 137 K. The Fe moments order AFM in the well-known stripe-like structure in the (ab) plane, but change from AFM to ferromagnetic (FM) arrangeme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 29 publications
11
53
0
Order By: Relevance
“…Below T = 75 K, ρ(T ) increases again, showing similarities to LaFeAsO 2 , followed by a decrease at T < 18 K. The decrease of ρ(T ) changes slope towards lower temperature with a linear temperature dependece at T < 6 K. The onset of the anomaly at T ≈ 20 K is also observable in polycrystalline material where no data is reported for T ≤ 19 K 24 . A similar behavior was published for NdFeAsO, where the change of the magnetic structure of Fe at T = 15 K results in a significant decrease in the electrical resistivity of single-crystalline material with the current in the abplane 25 . The TbFeAsO single-crystal measured (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Below T = 75 K, ρ(T ) increases again, showing similarities to LaFeAsO 2 , followed by a decrease at T < 18 K. The decrease of ρ(T ) changes slope towards lower temperature with a linear temperature dependece at T < 6 K. The onset of the anomaly at T ≈ 20 K is also observable in polycrystalline material where no data is reported for T ≤ 19 K 24 . A similar behavior was published for NdFeAsO, where the change of the magnetic structure of Fe at T = 15 K results in a significant decrease in the electrical resistivity of single-crystalline material with the current in the abplane 25 . The TbFeAsO single-crystal measured (Fig.…”
Section: Resultssupporting
confidence: 78%
“…5,6 Therefore understanding the magnetism in the iron-based parent compounds can lead to insight about the mechanism that induces superconductivity by doping or pressure. 7,8 CeFeAsO is a typical example of rare-earth-containing RFeAsO, with a tetragonal-to-orthorhombic structural transition upon cooling at T S ≈ 150 K, which is followed by the onset of stripelike Fe AFM order below T N ≈ 140 K. 9,10 Long-range AFM ordering of Ce below T Ce ≈ 4 K was first reported in powder neutron diffraction studies proposing a Ce magnetic structure that required further confirmation. 10 This study also suggested that Ce-Fe coupling is relatively strong as it influences the magnetic Fe peaks above T Ce up to ≈20 K. Furthermore, in support of strong Fe-Ce coupling, μSR measurements 11 on polycrystalline CeFeAsO show a considerable 3d-4f hybridization that leads to a considerable staggered Ce magnetization up to almost 120 K, far above T Ce .…”
Section: Introductionmentioning
confidence: 99%
“…Specific heat data for CeFeAsO suggest that the onsets of SPT appear to be at the same temperature for both the single crystalline as well as poly crystalline sample; although the transition appears to be broader for the latter [13,14]. For polycrystalline PrFeAsO (T S , T N ) have been reported to be (153K, 127 K) [15], whereas the same is (142 K, 137 K) for single crystal of NdFeAsO [16]. For SmFeAsO (T S , T N ) is (175 K, 140 K) [17].…”
Section: Introductionmentioning
confidence: 95%
“…Subsequently, superconductivity has been reported in other RFeAs(O 1-x F x ) compounds with R = Ce, Pr, Nd, Sm, etc., and the reported values of T c are 41 K in CeFeAsO 0.84 F 0. 16 , 52 K in PrFeAsO 0.89 F 0.11 , 54.3 K in NdFeAsO 1-y , 55 K in SmFeAsO 0.9 F 0.1 , and 54 K in GdFeAsO 1-y [4]. By now the iron-based superconductors have been extended to a much larger group containing variety of materials, mainly, four prototypical families 1111, 122, 111, and 11 types, and further variations such as 42622-type iron pnictides and 122-type iron chalcogenides [4].…”
Section: Introductionmentioning
confidence: 99%